Numerical study of air flow in the human respiratory system with rhinitis. (August 2021) - Issakhov, Alibek; Mardieyeva, Aizhan; Zhandaulet, Yeldos; Abylkassymova, Aizhan
Abstract: Heating and moisturizing for the human respiratory system is the most important function of the nose. When a person becomes ill with diseases such as rhinitis, the behavior of the air flow changes greatly in the nasal airways. The purpose of this study is to evaluate the effect of the disease on the basis of the flow, heating and humidification characteristics of the air. Normal 3D geometry of the nasal cavity was digitized using real tomographic images. The numerical results of air flow simulation were compared by laboratory test measurements and numerical results of other authors. Then, computational studies were performed for the case of swollen mucous membrane of the nasal cavity. The directions of the air flow in the nasal cavity and the distribution of temperature and relative humidity with swollen walls are very different from the normal state of the nasal cavity. The numerical results of this work can facilitate the diagnosis of various diseases and may be useful for treatment planning.